2020
DOI: 10.1101/2020.12.21.423810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogen effector recognition-dependent association of NRG1 with EDS1 and SAG101 in TNL receptor immunity

Abstract: Plants utilise intracellular nucleotide-binding, leucine-rich repeat (NLR) immune receptors to detect pathogen effectors and activate local and systemic defence. NRG1 and ADR1 "helper" NLRs (RNLs), cooperate with enhanced disease susceptibility 1 (EDS1), senescence-associated gene 101 (SAG101) and phytoalexin-deficient 4 (PAD4) lipase-like proteins to mediate signalling from TIR domain NLR receptors (TNLs). However, the mechanism of RNL/ EDS1 family protein cooperation is poorly understood. Here, we provide ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 74 publications
4
22
0
Order By: Relevance
“…MHAL-induced necrosis and dwarfism were partially suppressed in nrg1 triple mutants and fully suppressed in adr1 nrg1 sextuple mutants ( Figure 3C), indicating that hNLRs are redundantly required for MHAL function. While the redundancy between the two subfamilies was in agreement with other findings (Lapin et al, 2020;Pruitt et al, 2020;Sun et al, 2020;Wu et al, 2019), the stronger suppression of the MHAL overexpression effects was somewhat surprising, since it is the ADR1 subfamily that has been primarily linked to SA signaling (Bonardi et al, 2011;Castel et al, 2019). Additional genetic analysis confirmed that MHAL overexpression defects were dependent on SA accumulation, as the phenotype was completely suppressed by expression of the bacterial salicylate hydroxylase gene bacterial nahG gene, which converts SA to catechol (Gaffney et al, 1993), similar to what has been reported for other lines with increased ACD6 activity (Lu et al, 2005(Lu et al, , 2003Rate et al, 1999;Todesco et al, 2014Todesco et al, , 2010 ( Figure 3-figure supplement 2).…”
Section: Genetic Characterization Of the Mha1 Paralog Mhalsupporting
confidence: 85%
See 1 more Smart Citation
“…MHAL-induced necrosis and dwarfism were partially suppressed in nrg1 triple mutants and fully suppressed in adr1 nrg1 sextuple mutants ( Figure 3C), indicating that hNLRs are redundantly required for MHAL function. While the redundancy between the two subfamilies was in agreement with other findings (Lapin et al, 2020;Pruitt et al, 2020;Sun et al, 2020;Wu et al, 2019), the stronger suppression of the MHAL overexpression effects was somewhat surprising, since it is the ADR1 subfamily that has been primarily linked to SA signaling (Bonardi et al, 2011;Castel et al, 2019). Additional genetic analysis confirmed that MHAL overexpression defects were dependent on SA accumulation, as the phenotype was completely suppressed by expression of the bacterial salicylate hydroxylase gene bacterial nahG gene, which converts SA to catechol (Gaffney et al, 1993), similar to what has been reported for other lines with increased ACD6 activity (Lu et al, 2005(Lu et al, , 2003Rate et al, 1999;Todesco et al, 2014Todesco et al, , 2010 ( Figure 3-figure supplement 2).…”
Section: Genetic Characterization Of the Mha1 Paralog Mhalsupporting
confidence: 85%
“…Since ACD6 is both a regulator and effector of SA responses (Lu et al, 2003; Rate et al, 1999; Tateda et al, 2014; Zhang et al, 2014), we were interested in the relationship between ACD6 and the EDS1/NRG1/ADR1 node of lipase-like proteins and so-called helper NLRs (hNLRs), a convergence point of both ETI and PTI signaling that controls both SA-dependent and -independent defenses (Cui et al, 2017; Lapin et al, 2020; Pruitt et al, 2020; Sun et al, 2020; Wu et al, 2019). To test the requirement of hNLRs for MHAL activity, we overexpressed MHAL in plants carrying different combinations of mutations in the ADR1 and NRG1 subfamilies of hNLRs (Wu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we provide evidence that Rysto mediates immune responses in EDS1-SAG101-NRG1 but not PAD4 dependent manner. A similar mechanism was described for another TNL, Roq1 (Sun et al, 2020).…”
Section: Discussionsupporting
confidence: 54%
“…Two sub-families of helper NLRs, HeLo domain family (NRG1s and ADR1s) and EDS1 family of plantspecific lipase-like proteins (EDS1, PAD4 and SAG101) mediate defence signalling downstream of sensor TIR-NLRs (Lapin et al, 2019). Recently, it was reported that two distinct modules (NRG1/EDS1/SAG101 and ADR1/EDS1/PAD4) are required for TNLs-mediated immunity (Sun et al, 2020). Here, we provide evidence that Rysto mediates immune responses in EDS1-SAG101-NRG1 but not PAD4 dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…tomato strain DC3000 carrying effector AvrRps4 or AvrRpt2 (recognised by CC-NLR RPS2) 61 . PAD4 is dispensable for RRS1/RPS4 mediated cell death but required for the resistance to DC3000 with AvrRps4 62 . RGA5 with a modified HMA domain can confer HR to a new ligand, AVR-PikD in N. benthamiana but does not confer resistance in the homologous rice system 53 .…”
Section: Discussionmentioning
confidence: 99%